Residential Schools as an example of the history of cultural genocide on the native population of Canada in 1831–1996 - Garnek, Joanna (Jednostka wobec globalnego wymiaru stosunków międzynarodowych, 2021)
Canada is perceived and created in social discourse as a state of prosperity and happiness. These are not randomly applied treatments. The turbulent history of colonialism, followed by cultural genocide and forced assimilation – of the people considered indigenous in these areas – is still in the minds of the indigenous people to this day. The residential school system created at the turn of 1831 is that part of the country’s history that took years to explain and study. Many of the indigenous Canadians living in the area, or their ancestors, have experienced the operation of the above-mentioned Residential School System. Attempts to forcibly „civilize” the Aboriginal people left significant traces in the mentality and perception of the nation. The issue of showing the truth and reconciliation, often mentioned in the text, has become a permanent feature of the policy pursued by those in power in Canada. The aim of this work was the need to show the problems and diversity of Canadian society and the history that has developed over the last few decades. An attempt to show the impact of historical events on the formation of today’s Indigenous Citizen and Government relations. The research method I adopted was the historical-legal method.